3D sponge-like nanoporous carbons via a facile synthesis for high-performance supercapacitors: direct carbonization of tartrate salt. (1st July 2015) - Luo, Heming; Yang, Yanfei; Zhao, Xia; Zhang, Jianqiang; Chen, Yanzheng
Abstract: We report the direct synthesis of 3D sponge-like nanoporous carbons via carbonization of tartrate salt, including potassium tartrate and sodium tartrate, in inert atmosphere without any activation. The carbonization temperature is a very important parameter that ensures formation of the desired carbon structures and enhances their electrochemical performance in supercapacitors. Given that alkali metal is present in the selected carbon precursor, high-temperature activation causes reaming of carbon-K-800-1 to achieve a high specific surface area of 1018 m 2 g −1, thereby rendering the material suitable for use as an electrode for supercapacitors. All of the aqueous measurements were performed in a three-electrode system with 6 M KOH as the electrolyte. Carbon-K-800-1 can deliver a high specific capacitance of 296 F g −1 (29.1 μF cm −2 ) at a constant charge–discharge current of 0.7 A g −1 ; this capacitance may be maintained at 213 F g −1 (20.9 μF cm −2 ) at 20 A g −1 . A long cycle stability of 95.1% capacitance retention was observed after 5000 charge–discharge cycles at a current density of 3 A g −1 .